2005
DOI: 10.1007/s10533-005-4566-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Watering and Soil Moisture on Mercury Emissions from Soils

Abstract: This paper presents data from experiments that measured Mercury (Hg) flux as a function of water addition and subsequent soil drying, and maintenance of soil water content over time utilizing small dynamic gas exchange chambers and large mesocosms. When soil surfaces were dry and water was added at an amount less than that necessary to saturate the soil an immediate large (relative to dry soil flux) release of Hg occurred. Diel Hg emissions from soils, unenriched (0.02 lg g À1 ) and enriched (3 lg g À1 ) in Hg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
96
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(109 citation statements)
references
References 30 publications
(40 reference statements)
10
96
3
Order By: Relevance
“…3a), as VWC receded down to 0.07. This is consistent with the laboratory results of Gustin and Stamenkovic (2005), who hypothesised that evaporation of soil water helps mobilise mercury adsorbed to soil matter upwards to the air-surface interface. In their study, a pulse of GEM emission was observed immediately after precipitation events, attributed to expulsion of soil GEM from within the pore space.…”
Section: Environmental Correlatessupporting
confidence: 92%
“…3a), as VWC receded down to 0.07. This is consistent with the laboratory results of Gustin and Stamenkovic (2005), who hypothesised that evaporation of soil water helps mobilise mercury adsorbed to soil matter upwards to the air-surface interface. In their study, a pulse of GEM emission was observed immediately after precipitation events, attributed to expulsion of soil GEM from within the pore space.…”
Section: Environmental Correlatessupporting
confidence: 92%
“…These would be similar to the study of Gustin and Stamenkovic (2005) and Xin et al (2007) which observed that the fluxes were enhanced gradually with the substrate moisture decreasing, and then the fluxes were decreased with the soil moisture continuous decreasing. Gustin and Stamenkovic (2005) and Briggs and Gustin (2013) supposed the possible reason that soil with high water volumes, the water will saturate the soil pores and inhibits the soil gas exchange with the atmosphere, inhibiting the mercury emissions from the saturated substrate, whereas we have not tested the soil saturation in the subtropical forest. Briggs and Gustin (2013) also suggested that soil moisture was the most important parameter predicting mercury flux and the evaporative stage of soil moisture was used to partition the parameters that are most important for controlling mercury flux as the soils dried.…”
Section: Influence Of Atmospheric Tgm On the Mercury Flux: Experimentssupporting
confidence: 87%
“…But it should be noted that these experiments were not conducted in the same external conditions and the synergistic influence with humidity on the flux may not remain the same (Park et al, 2014). These would be similar to the study of Gustin and Stamenkovic (2005) and Xin et al (2007) which observed that the fluxes were enhanced gradually with the substrate moisture decreasing, and then the fluxes were decreased with the soil moisture continuous decreasing. Gustin and Stamenkovic (2005) and Briggs and Gustin (2013) supposed the possible reason that soil with high water volumes, the water will saturate the soil pores and inhibits the soil gas exchange with the atmosphere, inhibiting the mercury emissions from the saturated substrate, whereas we have not tested the soil saturation in the subtropical forest.…”
Section: Influence Of Atmospheric Tgm On the Mercury Flux: Experimentsmentioning
confidence: 52%
See 2 more Smart Citations